Finite-dimensional pointed Hopf algebras over finite simple groups of Lie type I: non-semisimple classes in PSLn(q) - Andruskiewitsch, Nicolas (2015)
We show that Nichols algebras of most simple Yetter–Drinfeld modules over the projective special linear group over a finite field, corresponding to non-semisimple orbits, have infinite dimension. We spell out a new criterium to show that a rack collapses.